Knowledge, Attitude & Practices of Surgeons in the time of COVID-19 - Amir Jalil; Rahila Kanwal; Zeeshan Idrees; Kashif Mehmood Khan; Muhammad Naseem; Muhammad Safi Kamal (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Objective: The objective of the study was to determine the knowledge, attitude and practices of surgical interns, residents and surgeons in the time of COVID-19. Methods: A cross-sectional study was conducted on surgical interns, trainees, registrar and consultants working in public and private sector tertiary care hospitals of Karachi. The non-Convenience sampling technique is used. A total of 184 patients were included. The study was performed on assessing patients' demographics, basic knowledge and awareness of COVID 19 and individuals' practices toward COVID 19 in their professional routines. Data were stored and analyzed using IBMSPSS version 23.0. Pearson Chi Square test was used to test the association outcomes, awareness and attitude items on COVID-19 between private and public sector hospitals. P-values less than 0.05 were considered statistically significant Results: The study comprised a total of 184 participants. Mostly from public 115(63%) rest 69(37%) belonged private sector hospitals. Most respondents 122(66.3%) were aware of COVID 19 incubation, symptoms and the detection of patients at risk and modalities of transmission in operating rooms.Results showed among public vs Private sector hospitals (81.7% / 68.1%) were treating corona virus, there were (35.7% / 46.3%) screening and admitted the cases, (56.5% / 62.4) tentative numbers of COVID-19 cases reported range from 0-25, (40.9%/ 11.6%) surgeons were assigned additional duties for COVID -19 by hospital management found statistically significant with "p<0.01". Conclusion: It is concluded after this study that the surgeons in Pakistan are well aware of the situation, have adequate knowledge of the risk factors and symptoms of COVID-19. But statistically, probably because of limited resources and workload, there is a substantial gap in practices between public and private sector surgeons. There is also a dire need to develop local guidelines related to preventive measures in our health care systems according to our demands and supply.